Prevalence of Diabetic Foot Ulcer and Associated Factors among Adult Diabetic Patients Who Attend the Diabetic Follow-Up Clinic at the University of Gondar Referral Hospital, North West Ethiopia, 2016: Institutional-Based Cross-Sectional Study. (16th July 2017) - Mariam, Tesfamichael G.; Alemayehu, Abebaw; Tesfaye, Eleni; Mequannt, Worku; Temesgen, Kiber; Yetwale, Fisseha; Limenih, Miteku Andualem
Abstract : Diabetes mellitus is a metabolic disorder which is characterized by multiple long-term complications that affect almost every system in the body. Foot ulcers are one of the main complications of diabetes mellitus. However, there is limited evidence on the occurrence of foot ulcer and influencing factors in Ethiopia. An institutional-based cross-sectional study was conducted in Gondar University Hospital, Ethiopia, to investigate foot ulcer occurrence in diabetic patients. Systematic random sampling was used to select 279 study participants. Bivariate and multivariable logistic regression model was fitted to identify factors associated with diabetic foot ulcer. Odds ratio with 95% confidence interval was computed to determine the level of significance. Diabetic foot ulcer was found to be 13.6%. Rural residence [AOR = 2.57; 95% CI: 1.42, 5.93], type II diabetes mellitus [AOR = 2.58; 95% CI: 1.22, 6.45], overweight [AOR = 2.12; 95% CI: 1.15, 3.10], obesity [AOR = 2.65; 95% CI: 1.25, 5.83], poor foot self-care practice [AOR = 2.52; 95% CI: 1.21, 6.53], and neuropathy [AOR = 21.76; 95% CI: 8.43, 57.47] were factors associated with diabetic foot ulcer. Diabetic foot ulcer was found to be high. Provision of special emphasis for rural residence, decreasing excessive weight gain, managing neuropathy, and promoting foot self-care practice would decrease diabetic foot ulcer.